Feasibility of Automated Propofol Sedation for Transcatheter Aortic Valve Implantation: A Pilot Study. (November 2017) - Zaouter, Cédrick; Hemmerling, Thomas M.; Mion, Stefano; Leroux, Lionel; Remy, Alain; Ouattara, Alexandre
Abstract : BACKGROUND: Recently, several trials have shown that closed-loop sedation is feasible. No study has used automated sedation in extremely frail patients, such as those scheduled for transcatheter aortic valve implantation (TAVI). We developed and tested a novel automated sedation system for this kind of population and surgery. The system integrates a decision support system that detects respiratory and hemodynamic events via smart alarms, which provide pertinent/related clinical suggestions and treatment options. The main objective was the feasibility of closed-loop sedation, defined as successful automated sedation without manual override. Secondary qualitative observations were clinical and controller performance. METHODS: Twenty patients scheduled for elective TAVI were enrolled. Sedation was administered via a closed-loop delivery system designed for propofol. The clinical performance of sedation was the efficacy to maintain a bispectral index (BIS) of 65. To evaluate the sedation performance, BIS values were stratified into 4 categories: excellent, very good, good, and inadequate sedation control, defined as BIS values within 10%, ranging from 11% to 20%, ranging from 21% to 30%, or >30% from the target value, respectively. The controller performance was calculated using Varvel parameters. Critical respiratory and hemodynamic events were documented. The former was defined as peripheral oxygen saturation <92% and/or respiratory rate <8/min, whereas the latter was considered a mean arterial pressure <60 mm Hg and/or heart rate <40 bpm. RESULTS: Automated sedation was successful in 19 patients undergoing TAVI. One patient was excluded from the final analysis because of conversion to general anesthesia. The secondary observations revealed that the clinical performance allowed an excellent to good control during 69% (99% confidence interval, 53%–77%; interquartile range, 59%–79%) of the sedation time. Fifteen patients presented critical respiratory episodes, with a median of 3 events per hour of sedation. Six patients presented critical hemodynamic episodes, with a median of 2 events per hour of procedure. CONCLUSIONS: The automated closed-loop sedation system tested could be used successfully for patients scheduled for a TAVI procedure. The results showed a satisfactory clinical performance of sedation control. Abstract : Published ahead of print December 22, 2016.